A core model based on 3D printing and preparation method thereof

Through the core model preparation method based on 3D printing, the problem of poor homogeneity of rock samples in the prior art is solved, and the controllable and efficient core model preparation of mineral composition ratio is achieved, which is suitable for rock mechanics research in multiple fields.

CN118849137BActive Publication Date: 2025-02-11SHANGHAI ADVANCED RES INST CHINESE ACADEMY OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411328825.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-11
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The rock samples prepared in the prior art have poor homogeneity, and cannot accurately control the mineral composition ratio, microstructure and size, and cannot meet the needs of rock mechanics experiments.

Method used

Using the 3D printing-based core model preparation method, the printing slurry is formed by mixing bedrock powder and ligand powder, adding photocuring agent, additive and photoinitiator, and then ball milling and defoaming treatment is carried out, and the printing slurry is formed through 3D printing equipment. After printing and forming, degreasing and sintering are performed to prepare a core model with controllable mineral composition and microstructure.

Benefits of technology

The mineral composition ratio of the core model is adjustable, and multiple models can be printed at the same time during the preparation process. The prepared core model has perfect brittleness and compressive strength, can maintain stability in high temperature environments, and is suitable for rock mechanics, Research in the fields of petrophysics, geochemistry, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118849137B_ABST
    Figure CN118849137B_ABST
Patent Text Reader

Abstract

The present invention provides a core model based on 3D printing and a preparation method thereof, comprising the following steps: S1, mixing bedrock and ligand powder into a mixed powder, the bedrock powder comprising olivine, pyroxene and basic plagioclase, and the ligand powder being one or a combination of serpentine, talc, chlorite, quartz, alkali feldspar and biotite; S2, adding a photocuring agent to the mixed powder and stirring and mixing to obtain a first slurry; S3, adding an auxiliary agent to the first slurry, ball milling to obtain a second slurry; S4, adding a photoinitiator to the second slurry, ball milling to obtain a third slurry; S5, defoaming treatment to obtain a printing slurry; S6, adding the printing slurry to a 3D printing device, printing and forming to obtain a blank; S7, degreasing the blank under a nitrogen atmosphere, and then sintering to obtain a core model. The preparation method of the present invention is fast, simple, controllable and efficient, and the prepared core model has high brittleness, high compressive strength, and controllable mineral composition and microstructure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of earth science technology, and in particular relates to a core model based on 3D printing and a preparation method thereof. Background Art

[0002] 3D printing is highly sought after by researchers at home and abroad due to its advantages such as short production cycle, high printing model precision, diverse materials, and personalized printing, and has been widely used in surgical auxiliary tools, prosthetic limb manufacturing, industrial molds, customized production, building components, artistic creation, etc. Compared with traditional olivine rock sample preparation technology, 3D printing can achieve precise control of the composition, structure and size of the sample. The rock samples produced by 3D printing have the advantages of high repeatability and good homogeneity, thus showing great application potential in the fields of rock mechanical properties simulation and engineering tunnel simulation experiments.

[0003] However, due to the large size of rock particles and uncontrollable composition, the samples currently used in the laboratory are mostly composed of gypsum, polymers, ceramics, etc. The inconsistency of the raw material composition leads to the inability of the samples to completely restore the characteristics of the rock. The stress-strain curve characteristics and failure characteristics of the 3D printed gypsum samples are similar to those of natural rocks, but its brittleness is high, and its uniaxial compressive strength is less than 10MPa, so it cannot completely replace rocks; polylactic acid, as an elastic-plastic material, has low strength and good ductility. Compared with rocks, its mechanical properties are closer to metals; ceramics are closer to natural rocks in various mechanical properties than polymers, but their strength and brittleness are insufficient, and they are more susceptible to fracture under the influence of temperature. In general, the strength of current 3D printed products is close to that of soft rocks, and there has been no report on rock sample preparation technology that can be directly applied to rock mechanics experiments.

[0004] (Ultra) basic rock is a general term for ultrabasic rock and basic rock, which refers to a type of igneous rock. Its SiO2 content is not higher than 53%. The SiO2 content of ultrabasic rock is lower than 45%. It is mainly composed of olivine, pyroxene, and their alteration products, such as serpentine, talc, chlorite, etc. Its representative rock is peridotite-picrite, which is mostly dark gray-black in color; the SiO2 content of basic rock is 45%-53%, mainly composed of pyroxene and basic plagioclase, often containing a small amount of quartz, alkaline feldspar, biotite, olivine, etc. Its representative rock is gabbro, which is gray-black, coarse-crystalline or porphyritic structure. (Ultra) basic rock contains more silicate minerals containing Ca, Mg, and Fe, which can react quickly with carbonate formed by injecting CO2 to form stable carbonate minerals, thereby realizing mineralization in a relatively short period of time and permanently sealing CO2 in the formation. Studying the chemical reaction between the mineral composition of (ultra)basic rocks and CO2 is of great significance for the geological storage of CO2. The reliability of the characterization of mineralization reactions depends on the consistency of mineral composition and microstructure. However, the rock samples prepared by the rock sample preparation technology in the existing technology have poor homogeneity and cannot accurately control the mineral composition, microstructure and size of the samples.

[0005] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0006] In view of the shortcomings of the prior art described above, the object of the present invention is to provide a core model based on 3D printing and a preparation method thereof, so as to solve the problems that the rock samples prepared in the prior art have poor homogeneity and cannot control the mineral composition ratio, microstructure and size.

[0007] To achieve the above objectives and other related objectives, the present invention provides a method for preparing a core model based on 3D printing, the preparation method comprising the following steps:

[0008] S1. Mixing bedrock powder and ligand powder to form mixed powder, wherein the bedrock powder includes olivine, pyroxene and basic plagioclase, and the ligand powder is one or a combination of serpentine, talc, chlorite, quartz, alkali feldspar and biotite;

[0009] S2, adding a light curing agent to the mixed powder and stirring and mixing to obtain a first slurry;

[0010] S3, adding an auxiliary agent to the first slurry, and ball milling to obtain a second slurry;

[0011] S4, adding a photoinitiator to the second slurry, and ball milling to obtain a third slurry;

[0012] S5, the third slurry is subjected to defoaming treatment to obtain a printing slurry;

[0013] S6, adding the printing slurry into the 3D printing equipment, setting the printing program, and printing and molding to obtain a blank;

[0014] S7, placing the green body in a nitrogen atmosphere for degreasing, and then sintering to obtain a core model.

[0015] Preferably, the diameters of the bedrock powder and the ligand powder in step S1 are both in the range of 5 to 30 μm.

[0016] Preferably, the photocuring agent in step S2 includes one or a combination of 1,6-hexanediol diacrylate and tripropylene glycol diacrylate.

[0017] Preferably, the auxiliary agent in step S3 includes one or a combination of a dispersant, a leveling agent, and a wetting agent; wherein the dispersant includes one of the models KOS110, KOS163, KOS2000, and TEGO Dispers750, the leveling agent includes one of the models TEGO Rad 2100 and TEGO Glide450, and the wetting agent includes one of the models TEGO Wet270 and TEGODispers740.

[0018] Preferably, the ball milling in step S3 is performed using a vertical planetary ball mill, the ball milling rate is 300 rpm to 600 rpm, and the ball milling time is 20 hours to 30 hours.

[0019] Preferably, the photoinitiator in step S4 includes one or a combination of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 1-hydroxycyclohexyl benzophenone, and 2-hydroxy-2-methyl-1-phenylacetone.

[0020] Preferably, the ball milling time in step S4 is 30 minutes to 90 minutes.

[0021] Preferably, the defoaming treatment in step S5 includes one or a combination of adding a defoaming agent, ultrasonic treatment, and vacuum treatment; wherein the defoaming agent includes TEGO Foamex 825 or TEGO Foamex 1488.

[0022] Preferably, based on the volume percentage of the printing slurry obtained in step S5, in the printing slurry, the volume ratio of the photocuring agent is 55%~70%, the volume ratio of the auxiliary agent is 0.2%~2%, and the volume ratio of the photoinitiator is 1%~5%.

[0023] Preferably, the printing program in step S6 includes exposure time, light intensity value and printing layer thickness; the exposure time and light intensity value of the printing program are determined according to the light curing time and light intensity value of the printing paste, respectively, and the light curing time and light intensity value of the printing paste are obtained by thinly applying the printing paste on a glass slide to form a thin sheet, and using ultraviolet light to irradiate and perform light curing performance detection;

[0024] The exposure time in the printing program is greater than the light curing time of the printing paste obtained by detection, and the light intensity value in the printing program is greater than the light intensity value of the printing paste obtained by detection;

[0025] The thickness of the printed layer is 1.5 to 3 times the diameter of the mixed powder.

[0026] Preferably, the degreasing temperature in step S7 is the polymer cracking temperature of the sheet formed by the printing slurry, and the polymer cracking temperature of the sheet is obtained by performing a thermogravimetric analysis experiment on the sheet in an air atmosphere.

[0027] Preferably, the sintering temperature in step S7 is 10-200° C. lower than the melting temperature of the sheet.

[0028] The present invention also provides a core model, which is prepared by adopting the above-mentioned core model preparation method based on 3D printing.

[0029] As described above, the core model based on 3D printing and the preparation method thereof of the present invention have the following beneficial effects:

[0030] The preparation method of the core model based on 3D printing in the present invention has the advantages of being fast, simple, controllable and efficient. The printing slurry is prepared by adjusting the mineral composition, and then a 3D printing device is used to set the printing program for printing. After degreasing and sintering, a core model is prepared. The mineral composition ratio is adjustable, and multiple models can be printed simultaneously during the preparation process by setting the printing program; and the prepared core model has perfect brittleness and compressive strength, controllable mineral composition and microstructure, and can maintain stability in a high temperature environment. The preparation method in the present invention can be used for research in the fields of rock mechanics, rock physics, geochemistry, etc., and can provide customized core models with consistent physical and chemical properties such as modulus, mineral composition, porosity, permeability, and parameter consistency in batches. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The thermogravimetric analysis curve of the sheet in the specific embodiment 1 of the present invention under air atmosphere is shown.

[0032] Figure 2 The thermogravimetric analysis curve of the sheet in the specific embodiment 2 of the present invention under air atmosphere is shown. DETAILED DESCRIPTION

[0033] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0034] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.

[0035] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.

[0036] The present invention provides a method for preparing a core model based on 3D printing, comprising the following steps:

[0037] S1. Mixing bedrock powder and ligand powder to form mixed powder, wherein the bedrock powder includes olivine, pyroxene and basic plagioclase, and the ligand powder is one or a combination of serpentine, talc, chlorite, quartz, alkali feldspar and biotite;

[0038] S2, adding a light curing agent to the mixed powder and stirring to obtain a first slurry;

[0039] S3, adding an additive to the first slurry, and ball milling to obtain a second slurry;

[0040] S4, adding a photoinitiator to the second slurry, and ball milling to obtain a third slurry;

[0041] S5, the third slurry is subjected to defoaming treatment to obtain a printing slurry;

[0042] S6, adding the printing slurry into the 3D printing device, setting the printing program, and printing to obtain a blank;

[0043] S7. Place the green body in a nitrogen atmosphere for degreasing, and then sinter it to obtain a core model.

[0044] Specifically, the preparation method of the core model based on 3D printing in the present invention has the advantages of being fast, simple, controllable and efficient. The printing slurry is prepared by adjusting the mineral composition, and then a 3D printing device is used to set the printing program for printing. After degreasing and sintering, a core model is prepared. The mineral composition ratio can be adjusted, and the printing of multiple models can be achieved simultaneously during the preparation process by setting the printing program. It can provide customized core models with consistent physical and chemical properties such as modulus, mineral composition, porosity, permeability, etc. and parameters for research in the fields of rock mechanics, rock physics, geochemistry, etc. in batches.

[0045] As an example, the diameters of the basic rock powder and the ligand powder in step S1 are 5 to 30 μm.

[0046] Specifically, the diameters of the basic rock powder and the ligand powder in step S1 may include values ​​within any range such as 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc.

[0047] In addition, in the specific embodiment of the present invention, the ratio between the bedrock powder and the ligand powder is related to the content of silicon dioxide in the target rock. The ratio between the two can be adjusted according to actual needs to make it close to the target rock, and no excessive restrictions are made here; of course, the amount of ligand powder added can be 0. In addition, the ligand powder is mainly used to regulate the mineral composition in the printed core model. For example, peridotite will be altered to form serpentinite, and its mineral composition will change, but the main composition will remain unchanged.

[0048] As an example, the photocuring agent in step S2 includes one or a combination of 1,6-hexanediol diacrylate and tripropylene glycol diacrylate.

[0049] Specifically, photocuring agent is a kind of substance that can initiate polymerization reaction under the action of light. The role of these two photocuring agents in the photocuring system is to serve as auxiliary components of photoinitiators. They can quickly absorb light energy and convert it into free radicals under the action of ultraviolet light or visible light, thereby initiating polymerization reaction. Selecting a suitable photocuring agent is crucial to obtaining ideal curing speed, physical properties and chemical stability.

[0050] As an example, the auxiliary agent in step S3 includes one or a combination of a dispersant, a leveling agent, and a wetting agent; wherein the dispersant includes one of the models KOS110, KOS163, KOS2000, and TEGO Dispers750, the leveling agent includes one of the models TEGO Rad2100 and TEGO Glide450, and the wetting agent includes one of the models TEGO Wet270 and TEGO Dispers740.

[0051] Specifically, additives are used to improve product performance and processing characteristics, dispersants are used to prevent particle aggregation, thereby improving the uniformity and stability of materials, leveling agents are used to improve fluidity, and wetting agents are used to reduce the tension of slurry on the solid surface.

[0052] As an example, the ball milling in step S3 is performed using a vertical planetary ball mill, the ball milling rate is 300-600 rpm, and the ball milling time is 20 hours-30 hours.

[0053] Specifically, the ball milling rate may include any value within the range of 300rpm, 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, etc., and the ball milling time may include any value within the range of 20 hours, 22 hours, 24 hours, 26 hours, 28 hours, 30 hours, etc.; in addition, the ball milling medium used in the ball milling process is preferably alumina or artificial corundum with high rigidity.

[0054] As an example, the photoinitiator in step S4 includes one or a combination of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 1-hydroxycyclohexyl benzophenone, and 2-hydroxy-2-methyl-1-phenylpropanone.

[0055] Specifically, photoinitiators are a class of substances that can generate free radicals or ions under the action of light. They play a key role in the photocuring system and can quickly initiate polymerization reactions.

[0056] As an example, the ball milling time in step S4 is 30 minutes to 90 minutes.

[0057] Specifically, the ball milling time in step S4 may include values ​​within any range such as 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, etc.

[0058] As an example, the defoaming treatment in step S5 includes one or a combination of adding a defoaming agent, ultrasonic treatment, and vacuum treatment; wherein the defoaming agent includes TEGO Foamex 825 or TEGO Foamex 1488.

[0059] Specifically, defoaming agents are substances specially designed to reduce the surface tension of liquids, thereby eliminating or reducing foam; supersonic treatment usually refers to the use of ultrasonic technology to destroy foam. The high-frequency vibration of ultrasound can produce mechanical action and quickly break up the foam structure. Ultrasonic treatment can very effectively remove foam as small as microscopic level; vacuum treatment is to reduce the solubility of gas in liquid by reducing the pressure of the system, thereby promoting the rupture of foam. Vacuum treatment can remove foam without chemical additives.

[0060] As an example, based on the volume percentage of the printing slurry obtained in step S5, in the printing slurry, the volume ratio of the photocuring agent is 55% to 70%, the volume ratio of the auxiliary agent is 0.2% to 2%, and the volume ratio of the photoinitiator is 1% to 5%.

[0061] Specifically, in the printing slurry, the volume ratio of the photocuring agent may include a value within any range such as 55%, 60%, 65%, 67%, 70%, etc., the volume ratio of the auxiliary agent may include a value within any range such as 0.2%, 0.5%, 1%, 2%, etc., and the volume ratio of the photoinitiator may include a value within any range such as 1%, 2%, 3%, 4%, 5%, etc.

[0062] As an example, the printing program in step S6 includes exposure time, light intensity value and printing layer thickness; the exposure time and light intensity value are respectively the light curing time and light intensity value of the printing slurry, and the light curing time and light intensity value are obtained by thinly coating the printing slurry on a glass slide to form a thin sheet, and using ultraviolet light to irradiate and test the light curing performance; the printing layer thickness is 1.5 to 3 times the diameter of the mixed powder.

[0063] Specifically, the thickness of the printed layer is 1.5 times, 1.8 times, 2.0 times, 2.3 times, 2.5 times, 2.8 times, 3 times, etc., of the diameter of the mixed powder.

[0064] As an example, the degreasing temperature in step S7 is the polymer decomposition temperature of the sheet formed by the printing slurry, and the polymer decomposition temperature of the sheet is obtained by performing a thermogravimetric analysis experiment on the sheet in an air atmosphere.

[0065] Specifically, the purpose of degreasing is to remove organic additives (i.e., photoinitiators) contained in the green body. These organic substances will decompose or volatilize at high temperatures. The holding time during the degreasing process is preferably 250 minutes to ensure that the organic additives are completely removed.

[0066] As an example, the sintering temperature in step S7 is 10-200° C. lower than the melting temperature of the sheet (eg, 10° C., 30° C., 50° C., 100° C., 150° C., 180° C., 200° C., etc.).

[0067] Specifically, after debinding, the green body needs to be sintered to enhance its mechanical properties and complete densification. The melting temperature of the thin sheet can be obtained by looking up the melting temperature of the corresponding mineral.

[0068] The present invention also provides a core model, which is prepared by adopting the above-mentioned core model preparation method based on 3D printing.

[0069] In order to better understand the core model based on 3D printing and the preparation method thereof in the present invention, the core model based on 3D printing and the preparation method thereof in the present invention are described below with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present invention in any way. Example 1

[0070] This embodiment provides a method for preparing a core model based on 3D printing, and the preparation method comprises the following steps:

[0071] S1. Weigh 44.22 g of olivine powder with a diameter of 24 μm (the density of olivine powder is 3.3 g / cm 3 , the corresponding volume is 13.4 mL;

[0072] S2, adding 25.24 mL of a photocuring agent (1,6-hexanediol diacrylate, density of 1.03 g / mL) to the olivine powder and stirring to obtain a first slurry;

[0073] S3, adding 0.1 mL of a leveling agent (TEGO Glide450, density 1.03 g / mL) to the first slurry, and ball milling the slurry at a speed of 400 rpm for 28 hours using a vertical planetary ball mill to obtain a second slurry;

[0074] S4, add 0.55g of photoinitiator (2,4,6-trimethylbenzoyl-diphenylphosphine oxide, density 1.12 g / cm 3 , the corresponding volume is 0.49 mL), and ball milled for 30 minutes to obtain a third slurry;

[0075] S5, the third slurry is subjected to supersonic and vacuum treatment to obtain a printing slurry;

[0076] S6, dip the printing slurry and apply it thinly on a glass slide to form a thin sheet, use ultraviolet light to test the light curing performance, and get a light curing time of 2 seconds and a light intensity of 4; add the printing slurry to the 3D printing device, set the printing program (exposure time 3 seconds, light intensity 6, printing layer thickness 50 μm) according to the light curing time and light intensity value obtained by the test, and print to obtain a blank;

[0077] S7. The slice was placed in air atmosphere for thermogravimetric analysis, and the polymer pyrolysis temperature of the slice was found to be 305°C (see Figure 1 ), the green body was placed in a nitrogen atmosphere for degreasing, the degreasing temperature was set to 305°C, and the temperature was kept for 250 minutes. The speed reduction sections were set at 250°C, 300°C and 480°C respectively to prevent the green body from cracking during degreasing. The degreased model was then placed in an air atmosphere and heated to 1400°C and kept for 120 minutes to obtain a core model. Example 2

[0078] This embodiment provides a method for preparing a core model based on 3D printing, and the preparation method comprises the following steps:

[0079] S1. Weigh 60.77 g of olivine powder with a diameter of 13 μm (density of 3.3 g / cm 3 , the corresponding volume is 18.5 mL) and 0.92 g of ligand powder (serpentine, with a density of 2.6 g / cm 3 , the corresponding volume is 0.28 mL), to form a mixed powder;

[0080] S2, adding 40.08 mL of a photocuring agent (1,6-hexanediol diacrylate, density 1.03 g / mL) to the mixed powder and stirring to obtain a first slurry;

[0081] S3, adding 1.25 mL of a leveling agent (TEGO Glide450, density 1.03 g / mL) to the first slurry, and ball milling the slurry at a speed of 400 rpm for 24 hours using a vertical planetary ball mill to obtain a second slurry;

[0082] S4, add 2.86g of photoinitiator (2,4,6-trimethylbenzoyl-diphenylphosphine oxide, density 1.12 g / cm 3 , the corresponding volume is 2.55 mL), and ball milled for 30 minutes to obtain a third slurry;

[0083] S5, the third slurry is subjected to supersonic and vacuum treatment to obtain a printing slurry;

[0084] S6, dip the printing slurry and apply it thinly on a glass slide to form a thin sheet, use ultraviolet light to irradiate and test the light curing performance, and the light curing time is 2 seconds and the light intensity value is 4; add the printing slurry to the 3D printing equipment, set the printing program according to the light curing time and light intensity value obtained by the test (exposure time 3 seconds, light intensity value 6, printing layer thickness of 25μm), and print to obtain a blank;

[0085] S7. The slice was placed in air atmosphere for thermogravimetric analysis, and the polymer pyrolysis temperature of the slice was found to be 310°C (see Figure 2 ), the green body was placed in a nitrogen atmosphere for degreasing, the degreasing temperature was set to 310°C, and the temperature was kept for 250 minutes. The speed reduction sections were set at 250°C, 300°C and 480°C respectively to prevent the green body from cracking during degreasing. The degreased model was then placed in an air atmosphere, heated to 1400°C and kept for 120 minutes to obtain a core model. Example 3

[0086] This embodiment provides a method for preparing a core model based on 3D printing, and the preparation method comprises the following steps:

[0087] S1. Weigh 48.24 g of pyroxene powder with a diameter of 24 μm (density of 3.6 g / cm 3 , the corresponding volume is 13.4mL);

[0088] S2, adding 25.24 mL of a photocuring agent (1,6-hexanediol diacrylate, density 1.03 g / mL) to the pyroxene powder and stirring to mix to obtain a first slurry;

[0089] S3, adding 0.5 mL of a leveling agent (TEGO Glide450, density 1.02 g / mL) to the first slurry, and ball milling the mixture at 400 rpm for 28 hours using a vertical planetary ball mill to obtain a second slurry;

[0090] S4, add 0.49g of photoinitiator (2,4,6-trimethylbenzoyl-diphenylphosphine oxide, density 1.12 g / cm 3 , the corresponding volume is 0.44 mL), and ball milled for 30 minutes to obtain a third slurry;

[0091] S5, the third slurry is subjected to supersonic and vacuum treatment to obtain a printing slurry;

[0092] S6, dip the printing slurry and apply it thinly on a glass slide to form a thin sheet, use ultraviolet light to test the light curing performance, and get a light curing time of 2 seconds and a light intensity of 4; add the printing slurry to the 3D printing device, set the printing program (exposure time 3 seconds, light intensity 6, printing layer thickness 50 μm) according to the light curing time and light intensity value obtained by the test, and print to obtain a blank;

[0093] S7. The slice was placed in an air atmosphere for a thermogravimetric analysis experiment, and the cracking temperature of the slice was obtained to be 305°C. The green body was placed in a nitrogen atmosphere for degreasing, and the degreasing temperature was set to 305°C, and kept warm for 250 minutes. The speed reduction sections were set at 250°C, 300°C and 480°C respectively to prevent the green body from cracking during degreasing. The degreased model was then placed in an air atmosphere, heated to 1300°C and kept warm for 120 minutes to obtain a core model. Example 4

[0094] This embodiment provides a method for preparing a core model based on 3D printing, and the preparation method comprises the following steps:

[0095] S1. Weigh 36.98 g of basic plagioclase powder with a diameter of 24 μm (density of 2.76 g / cm 3 , the corresponding volume is 13.4mL);

[0096] S2, adding 25.24 mL of a photocuring agent (1,6-hexanediol diacrylate, density 1.03 g / mL) to the basic plagioclase powder and stirring to mix, to obtain a first slurry;

[0097] S3, adding 0.1 mL of a leveling agent (TEGO Glide450, density 1.03 g / mL) to the first slurry, and ball milling the mixture at 400 rpm using a planetary ball mill for 28 hours to obtain a second slurry;

[0098] S4, add 0.49g of photoinitiator (2,4,6-trimethylbenzoyl-diphenylphosphine oxide, density 1.12 g / cm 3 , the corresponding volume is 0.44 mL), and ball milled for 30 minutes to obtain a third slurry;

[0099] S5, the third slurry is subjected to supersonic and vacuum treatment to obtain a printing slurry;

[0100] S6, dip the printing slurry and apply it thinly on a glass slide to form a thin sheet, use ultraviolet light to test the light curing performance, and get a light curing time of 2 seconds and a light intensity of 4; add the printing slurry to the 3D printing device, set the printing program (exposure time 3 seconds, light intensity 6, printing layer thickness 50 μm) according to the light curing time and light intensity value obtained by the test, and print to obtain a blank;

[0101] S7. The slice is placed in an air atmosphere for a thermogravimetric analysis experiment, and the cracking temperature of the slice is obtained to be 305°C. The green body is placed in a nitrogen atmosphere for degreasing, and the degreasing temperature is set to 305°C, and the temperature is kept for 250 minutes. The speed reduction sections are set at 250°C, 300°C and 480°C respectively to prevent the green body from cracking during degreasing. The green body is placed in a nitrogen atmosphere for degreasing, and then the degreased model is placed in an air atmosphere, heated to 1050°C and kept warm for 120 minutes to obtain a core model.

[0102] The core models prepared in Examples 1 to 4 were subjected to uniaxial compression tests using a pressure testing machine to obtain the brittleness and compressive strength of the core models. The results are shown in Table 1.

[0103] Table 1. Brittleness and compressive strength of the core models prepared in Examples 1 to 4

[0104] project Brittle / Plastic Compressive strength / MPa Example 1 brittleness 148 Example 2 brittleness 127 Example 3 brittleness 175 Example 4 brittleness 155

[0105] In summary, the preparation method of the core model based on 3D printing in the present invention has the advantages of being fast, simple, controllable and efficient. The printing slurry is prepared by adjusting the mineral composition, and then a 3D printing device is used to set the printing program for printing. After degreasing and sintering, a core model is prepared, and its mineral composition ratio is adjustable. During the preparation process, the printing of multiple models can be realized simultaneously by setting the printing program; and the prepared core model has perfect brittleness and compressive strength, has controllable mineral composition and microstructure, and can maintain stability in a high temperature environment. The preparation method in the present invention is for research in the fields of rock mechanics, rock physics, geochemistry, etc., and provides customized core models with consistent physical and chemical properties such as modulus, mineral composition, porosity, and permeability in batches. Therefore, the present invention effectively overcomes the various shortcomings in the prior art and has a high industrial utilization value.

[0106] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a core model based on 3D printing, characterized in that: The preparation method comprises the following steps: S1. Mixing bedrock powder and ligand powder to form mixed powder, wherein the bedrock powder includes olivine, pyroxene and basic plagioclase, and the ligand powder is one or a combination of serpentine, talc, chlorite, quartz, alkali feldspar and biotite; the diameters of the bedrock powder and the ligand powder in step S1 are both in the range of 5 μm to 30 μm; S2, adding a light curing agent to the mixed powder and stirring and mixing to obtain a first slurry; S3, adding an auxiliary agent to the first slurry, and ball milling to obtain a second slurry; S4, adding a photoinitiator to the second slurry, and ball milling to obtain a third slurry; S5, the third slurry is subjected to defoaming treatment to obtain a printing slurry; based on the volume percentage of the printing slurry obtained in step S5, in the printing slurry, the volume ratio of the photocuring agent is 55% to 70%, the volume ratio of the auxiliary agent is 0.2% to 2%, and the volume ratio of the photoinitiator is 1% to 5%; S6, adding the printing slurry to the 3D printing equipment, setting the printing program, and printing and molding to obtain a blank; the printing program in step S6 includes exposure time, light intensity value and printing layer thickness; the exposure time and light intensity value of the printing program are determined according to the light curing time and light intensity value of the printing slurry, respectively, and the light curing time and light intensity value of the printing slurry are obtained by thinly applying the printing slurry on a glass slide to form a thin sheet, and using ultraviolet light to irradiate and perform light curing performance detection; the exposure time in the printing program is 1.2 to 1.8 times the light curing time of the printing slurry obtained by detection, and the light intensity value in the printing program is 1.2 to 1.8 times the light intensity value of the printing slurry obtained by detection; the printing layer thickness is 1.5 to 3 times the diameter of the mixed powder; S7. Degreasing the green body in a nitrogen atmosphere, and then sintering it to obtain a core model; the degreasing temperature is the polymer cracking temperature of the sheet formed by the printing slurry, and the polymer cracking temperature of the sheet is obtained by performing a thermogravimetric analysis experiment on the sheet in an air atmosphere.

2. The method for preparing a core model based on 3D printing according to claim 1, characterized in that: The photocuring agent in step S2 includes one or a combination of 1,6-hexanediol diacrylate and tripropylene glycol diacrylate.

3. The method for preparing a core model based on 3D printing according to claim 1, characterized in that: Step S3 includes one or a combination of the following conditions: The auxiliary agent includes one or a combination of a dispersant, a leveling agent, and a wetting agent; wherein the dispersant includes one of the models KOS110, KOS163, KOS2000, and TEGO Dispers750; the leveling agent includes one of the models TEGO Rad 2100 and TEGOGlide450; and the wetting agent includes one of the models TEGO Wet270 and TEGO Dispers740; The ball milling is performed using a vertical planetary ball mill, the ball milling rate is 300 rpm to 600 rpm, and the ball milling time is 20 hours to 30 hours.

4. The method for preparing a core model based on 3D printing according to claim 1, characterized in that: Step S4 includes one or a combination of the following conditions: The photoinitiator includes one or a combination of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide, 1-hydroxycyclohexyl benzophenone, and 2-hydroxy-2-methyl-1-phenylacetone; The ball milling time is 30 minutes to 90 minutes.

5. The method for preparing a core model based on 3D printing according to claim 1, characterized in that: The defoaming treatment in step S5 includes one or a combination of adding a defoaming agent, supersonic treatment, and vacuum treatment; wherein the defoaming agent includes TEGO Foamex 825 or TEGO Foamex 1488.

6. The method for preparing a core model based on 3D printing according to claim 1, characterized in that: The sintering temperature in step S7 is 10° C. to 200° C. lower than the melting temperature of the sheet.

7. A core model, characterized in that: The core model is prepared by the core model preparation method based on 3D printing described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Random structural plane network contained rock mass model 3D printing and mechanical parameter acquisition method

    CN113146797A

  • Method for determining DLP ceramic photocuring 3D printing parameters

    CN117484635A